Cyberbullying and its relationship to negative thinking among Hail University female students - Al-Rashed, Ashwag Fayz; Al-Rashedy, Benayan Bani (Journal of Educational and Psychological Sciences, 2025)
The study aimed to measure the level of cyberbullying and negative thinking, and their relationship, in addition to revealing the differences resulting from academic specialization (natural sciences, humanities) and the impact of cyberbullying on negative thinking among female students at the University of Hail. The researchers used the descriptive correlational approach, where two scales were applied: the Cyberbullying Scale and the Negative Thinking Scale, to a stratified random sample of 154 female students. The results showed a low level of cyberbullying and negative thinking among the students in the different academic specializations. The study also revealed a strong positive correlation between cyberbullying and negative thinking, which was statistically significant at (α ≥ 0.05). Regarding academic specialization, no statistically significant differences were found in the level of cyberbullying or negative thinking among the students based on their specialization (humanities - natural sciences). The results of the simple linear regression analysis confirmed that an increase of one unit in the level of cyberbullying is associated with an increase of 0.920 units in negative thinking. Based on the study's findings, the researchers recommended including methods of confronting cyberbullying in the curricula at its various stages, with the aim of keeping pace with the latest developments that require intellectual and behavioral awareness. They also suggested conducting a study on cyberbullying on larger samples of undergraduate students that include both males and females and studying the differences between them, and studying the various psychological effects of cyberbullying, whether for the bully or the victim.
Keywords: Cyberbullying; negative thinking; Hail University female students